1981
DOI: 10.1016/s0072-968x(81)80060-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemosurgical Excision of Subungual Squamous Cell Carcinoma

Abstract: Chemosurgery and wound healing by secondary intention is an excellent method of treatment for subungual carcinoma. It allows for complete ablation of the tumour with maximal preservation of tissue, eliminating the need for amputation, in the absence of bone involvement. As most nail bed carcinomas occur on the thumb, by avoiding distal phalanx amputation one can prevent considerable disability. Because chemosurgery traces out every infiltrating band of tumour, bone involvement can be accurately detected. Amput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The advantage of the Mohs technique over a conventional surgical approach comes to bear particularly in the treatment of malignant lesions involving such sensitive areas as the fingers and nails 5 . The three‐dimensional histographic tracing of the tumor utilized in Mohs microscopically controlled surgery accomplishes at least three goals.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the Mohs technique over a conventional surgical approach comes to bear particularly in the treatment of malignant lesions involving such sensitive areas as the fingers and nails 5 . The three‐dimensional histographic tracing of the tumor utilized in Mohs microscopically controlled surgery accomplishes at least three goals.…”
Section: Discussionmentioning
confidence: 99%
“…Tomisk et al retrospectively reviewed 8 patients with subungual SCC treated with MMS and found a 100% DFS at follow-up times ranging from 3 months to 5 years. 41 In a retrospective review of 414 patients with SCC treated with MMS, Robins et al found a recurrence rate of 3.4% at an average follow-up of 18.6 months, including a recurrence rate of just 2.4% in patients with upper extremity SCC. 42 …”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%
“…The age of onset usually ranges from 50 to 60 years, although the youngest patient reported was only 20 years old at the time of diagnosis 4 . Squamous‐cell carcinoma of the nail bed is uncommon: Only four cases were found by Einchenholz and DeAngelis in their study of a consecutive series of 280,000 hospital admissions for cutaneous carcinoma, 5 and in another series only eight cases were found in more than 3,000 patients who had cancers of the skin 6 …”
Section: Introductionmentioning
confidence: 99%